Antioxidant Potential of the Sweet Whey-Based Beverage Colada after the Digestive Process and Relationships with the Lipid and Protein Fractions - Victoria E. García-Casas; Isabel Seiquer; Zaira Pardo; Ana Haro; Isidra Recio; Raquel Olías (MDPI AG, 2022)
Whey-based beverages could be an effective way of reusing a by-product of th cheese industry, mitigating environmental hazards and, at the same time, profiting a useful food with high nutritional and antioxidant properties. In this study, a traditional Ecuadorian beverage (Colada) was prepared combining sweet whey, Maracuyá and barley. Antioxidant properties before and after an in vitro digestion using the INFOGEST method were determined, and relationships with intestinal transformations of the lipid and protein fractions were analyzed. The digestive process had a positive effect on antioxidant properties based on increased values of ABTS and FRAP located in the bioaccessible fraction (BF), together with strong increments of total polyphenols. Moreover, pretreatment of Caco-2 cells with the BF of Colada significantly reduced ROS generation (p < 0.001) measured by the dichlorofluorescein assay. Substantial changes of the fatty acid profile occurred during digestion, such as a fall of saturated fatty acids and a rise of polyunsaturated. The protein profile, examined by SDS-PAGE and exclusion molecular chromatography in the BF, showed that the major part of the proteins were digested in the intestinal phase. Analysis of NanoLC-MS/MS revealed 18 antioxidant peptides originated from whey proteins, but also 16 peptides from barley with potential antioxidant properties. In conclusion, combining sweet whey with Maracuyá and barley constitutes an excellent nutritional beverage with a strong antioxidant potential.